Composite Superelastic Aerogel Scaffolds Containing Flexible SiO2 Nanofibers Promote Bone Regeneration. Issue 15 (19th June 2022) - Liu, Mingyue; Shafiq, Muhammad; Sun, Binbin; Wu, Jinglei; Wang, Wei; EL‐Newehy, Mohamed; EL‐Hamshary, Hany; Morsi, Yosry; Ali, Onaza; Khan, Atta ur Rehman; Mo, Xiumei
Abstract: Repairing irregular‐shaped bone defects poses enormous challenges. Scaffolds that can fully fit the defect site and simultaneously induce osteogenesis and angiogenesis hold great promise for bone defect healing. This study aimed to produce superelastic organic/inorganic composite aerogel scaffolds by blending silica nanofibers (SiO2 ) and poly (lactic acid)/gelatin (PLA/gel) nanofibers; the content of SiO2 nanofibers is varied from 0–60 wt% (e.g., PLA/gel, PLA/gel/SiO2 ‐L, PLA/gel/SiO2 ‐M, and PLA/gel/SiO2 ‐H for 0%, 20%, 40%, and 60% of SiO2 nanofibers, respectively) to produce a range of scaffolds. The PLA/gel/SiO2 ‐M scaffold has excellent elasticity and good mechanical properties. In vitro experiments demonstrate that the silicon ions released from PLA/gel/SiO2 ‐M scaffolds promote the differentiation of rat bone marrow‐derived mesenchymal stem cells into osteoblasts, enhancing alkaline phosphatase activity and bone‐related genes expressions. The released silicon ions also promote the proliferation of human umbilical vein endothelial cells and the expression of vascular endothelial growth factors, thereby promoting angiogenesis. The assessment of these scaffolds in a calvarial defect model in rats shows good potential of PLA/gel/SiO2 ‐M to induce bone regeneration as well as promote osteogenesis and angiogenesis. Overall, these organic/inorganic composite scaffolds have good biological activity, which may have broad applications for tissue engineering. Abstract : The preparation of organic–inorganic hybrid aerogel scaffolds with superelasticity and porous structure for bone regeneration is shown by hybrid thermal crosslinking of organic PLA/gel electrospun short nanofibers and flexible SiO2 electrospun short nanofibers. The silicon ions released from the PLA/gel/SiO2 aerogel scaffolds promote the formation of blood vessels and the expression of bone‐related genes, promoting the regeneration of rat calvaria.